2020
DOI: 10.3390/en13020336
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Environmental Aspects of an Electric Bus Fleet Under Service

Abstract: The reduction of pollutant emissions in the field of transportation can be achieved by developing and implementing electric propulsion technologies across a wider range of transportation types. This solution is seen as the only one that can offer, in areas of urban agglomeration, a reduction of the emissions caused by the urban transport to zero, as well as an increase in the degree of the health of the citizens. This paper presents an analysis of the direct and indirect environmental aspects of a fleet of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Table 4 presents a comparison with other assessments on the influence of moving to electric vehicles. Minet [46] applied an approach based on changes in emissions when assessing the effects in São Paulo (Brazil) and Cluj-Napoca (Romania), respectively. These assessments, summarized in Table 4, reported decreases in NOx emissions.…”
Section: Shift From Diesel To Electric Busesmentioning
confidence: 99%
“…Table 4 presents a comparison with other assessments on the influence of moving to electric vehicles. Minet [46] applied an approach based on changes in emissions when assessing the effects in São Paulo (Brazil) and Cluj-Napoca (Romania), respectively. These assessments, summarized in Table 4, reported decreases in NOx emissions.…”
Section: Shift From Diesel To Electric Busesmentioning
confidence: 99%
“…In terms of environmental impact assessment, Todorut et al [4] believe that public transport needs to alleviate the problem of carbon emission pollution and use CO 2 emissions as an evaluation indicator for pure electric buses. Subsequently, Varga et al [5] increased the NOx emission indicator. On this basis, Shauna et al [6] used fuel economy and emission efficiency as evaluation indicators, conducted comparison experiments between pure electric buses and diesel buses in the cities of Nevada and Iowa, and found that the fuel economy of electric buses increased by at least 29%.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the study [8] work on a real case by monitoring an electric bus fleet and analyzing the direct and indirect environmental aspects impacting the emission and health of citizens in Cluj-Napoca, Romania. Study [9] presents a new paradigm regarding Electric Vehicles (EVs) and the management distribution grids.…”
Section: Introductionmentioning
confidence: 99%